River valleys as the object of ecological and geobotanical research - Дідух, Я.П.; Чусова, О.О.; Ольшевська, І.А.; Поліщук, Ю.В. (Український ботанічний журнал, 2015)
The river valleys are characterized by high diversity of ecosystems, their originality, complex structure and
dynamics. Changes in vertical displacements from the plain to channel in various parts of сatena, which
can be seen as an intricate complex integrating coenoses formation, geomorphological and pedogenic
processes, are very important. Plant communities serve as indicators of territorial and temporal changes.
Combinations of the communities within the ecological series influenced by environmental factors
are characterized as ‘ecomers’, which reflect the trends of ecosystem changes, i.e. ȕ-coenodiversity.
Quantitative assessment of these plant communities is possible based on the synphytoindication
methodology. There were selected three model river valleys, namely, those of the Sluch, Dniester, and
Krasna rivers. Comparison of these rivers is of a special interest because they have different dimensions
and flow in different natural areas. The topological differentiation in ecological series of the river valleys
served for comparison of the ‘ecomers’, i.e. for assessment of ȕ-coenodiversity differentiation towards
changes of leading ecological factors. Долини річок характеризуються високою різноманітністю екосистем, їх оригінальністю, складною структурованістю і динамічністю. Важливе значення у формуванні закономірностей територіального розподілу цих екосистем мають вертикальні переміщення від плакору до русла на різних ділянках катени, яку можна розглядати як складний комплекс, де інтегруються геоморфологічні, грунтотвірні процеси та ценозоутворення. Індикаторами цих територіально-часових змін виступають відповідні рослинні угруповання, поєднання яких у межах екологічного ряду під впливом екологічних чинників трактується як екомери, що відображає градієнт змін, тобто beta-різноманіття. Кількісна оцінка цих рослинних угруповань можлива на основі методики синфітоіндикації. Для роботи було обрано 3 модельні річки (Случ, Дністер і Красна), які мають різну розмірність і протікають у різних природних зонах. На їх прикладі проведено порівняння екомерів, тобто оцінено диференціацію beta-ценорізноманіття щодо зміни провідних екофакторів. Долины рек характеризуются высоким разнообразием
экосистем, их оригинальностью, сложной структурированностью и динамичностью. Важное значение в
формировании закономерностей территориального
распределения этих экосистем имеют вертикальные
перемещения от плакора до русла на разных участках
катены, которую можно рассматривать как сложный
комплекс, где интегрируются геоморфологические,
почвообразующие и процессы ценозообразования.
Индикаторами этих территориально-временных
изменений выступают соответствующие растительные
сообщества, сочетание которых в пределах
экологического ряда под влиянием экологических
факторов трактуется как экомеры, что отражает
градиент изменений, то есть ȕ-ценоразнообразие.
Количественная оценка этих растительных сообществ
возможна на основе методики синфитоиндикации.
Для работы были выбраны три модельные реки (Случ,
Днестр и Красная), которые имеют разную размерность
и протекают в разных природных зонах. На их примере
проведено сравнение экомеров, т. е. дана оценка
дифференциации ȕ-ценоразнообразия по отношению к
изменению ведущих экофакторов.